Method of operator processes images and signals without computing integrals of Laplace - Єгоршин, Ю.О.; Красноусова, О.Ю. (Proceedings of National Aviation University (archive), 2007)
This method allow us to find the expression of operational representations of processes and signals without calculation of the Laplace’s integrals. This method comfortably can be used if process or signal is described on area of regularity by harmonious, exponential and polynomial time functions and also by theirs combinations.